Making "himself" tattoo: trace and writing in the body boards - Costa, Ana Maria Medeiros da (Clinical Styles. The Journal on the vicissitudes of childhood, 2002)
This article treats the research of the function of the tattoo, in his determinations symbolical, imaginary and real. Takes the instinct body boards, as well as a body writing determ in a tion and the trace of other looking. Treats the generality function of tattoo, in the cultural singularity, as well as the particularity of his meaning in the adolescence.